PATRIARCHAL CULTURAL REPRESENTATION IN THE PROTESTANT CHRISTIAN CHURCH COMMUNITY IN BALI (GKPB) - Made Narawati; I Nyoman Suarka; Ni Made Wiasti (E-Journal of Cultural Studies, 2021)
The Protestant Christian Church in Bali (GKPB) is the largest Protestant Church in Bali. The Protestant Christian Church in Bali (GKPB), in determining the number of strategic officials, refers to the 2014 Church Order regarding membership in Article 107 paragraph 1, 8 (eight) people elected at the Synod session must consist of at least 2 female elements and 1 youth element . Complete Synod Council Personnel (MSL-GKPB) Head of Departments and Chair of Special Institutions, 2016-2020 period, totaling 30 people; 27 men (90%), while only three women (10%). The patriarchal culture is very strong in determining strategic positions in GKPB resulting in male domination in leadership structures and policies that tend to be gender biased. With qualitative methods and using the Theory of Power-Knowledge Relationships Michel Foucault, According to Foucault, knowledge and power have a reciprocal relationship. Continuous violation of power will create a form of knowledge, and vice versa, the administration of knowledge will have an effect on power. The second is Pierre Bourdieu's Structural theory, which describes how symbolic violence and the division of roles in society shape habitus. Keywords: Representation, Patriarchy, Symbolic Violence